An analysis of satisfaction of passenger services offered in premium trains in Indian Railways with reference to northern zone. (12th October 2021) - Choudhary, Atul; Bansal, Sanjeev; Prashaant, Anu; Sharma, Prashant
Due to the growing importance of quality in our life, customers' desire to enjoy a relatively better quality of products or availing superior quality services has been increased. India is the second highly populated country of the world and its rapid population growth also contributes to an increase of people's travelling demands. In India, trains are the cheapest and comfortable mode of travelling especially for long distances. This paper aims to investigate the passengers' perceptions about the service quality of premium trains of northern zone of Indian Railways. The present paper highlights the prominent dimensions in determining the passengers' overall perceived service quality offered by the premium trains of northern railways. The main intent of this study is to present a framework developed for assisting northern railways to monitor and control the quality of services provided to passengers of premium trains such as Rajdhani and Shatabdi Express.